THE TOPOLOGICAL SUBGROUP'S REFLECTIVE CATEGORY - Tuteja, Amit; Rakshit, Madhuchanda (International Journal of Psychosocial Rehabilitation, 2021)
Endomorphism monoids have long piqued the curiosity of researchers in both universal algebra and specific classes of algebraic structures. Endomorphism monoids have long piqued the curiosity of researchers in both universal algebra and specific classes of algebraic structures. The collection of endomorphisms for any algebra is closed under composition and forms a monoid (that is, a semigroup with identity). The endomorphism monoid is a fascinating structure that can be obtained from a given algebra. The structure and features of the endomorphism monoid of a strong semilattice of left simple semigroups are investigated in this research. In such a semigroup, the defining homomorphisms are primarily constant or bijective.